Radiation dose-fractionation in adult Aedes aegypti mosquitoes - Yamada Hanano; Maïga Hamidou; Kraupa Carina; Somda Nanwintoum Séverin Bimbilé; Mamai Wadaka; Wallner Thomas; Bouyer Jeremy (Parasite, 2023)
Balancing process efficiency and adult sterile male biological quality is one of the challenges in the success of the sterile insect technique (SIT) against insect pest populations. For the SIT against mosquitoes, many stress factors need to be taken into consideration when producing sterile males that require high biological quality to remain competitive once released in the field. Pressures of mass rearing, sex sorting, irradiation treatments, packing, transport and release including handling procedures for each step, add to the overall stress budget of the sterile male post-release. Optimizing the irradiation step to achieve maximum sterility while keeping off-target somatic damage to a minimum can significantly improve male mating competitiveness. It is therefore worth examining various protocols that have been found to be effective in other insect species, such as dose fractionation. A fully sterilizing dose of 70 Gy was administered to Aedes aegypti males as one acute dose or fractionated into either two equal doses of 35 Gy, or one low dose of 10 Gy followed by a second dose of 60 Gy. The two doses were separated by either 1- or 2-day intervals. Longevity, flight ability, and mating competitiveness tests were performed to identify beneficial effects of the various treatments. Positive effects of fractionating dose were seen in terms of male longevity and mating competitiveness. Although applying split doses generally improved male quality parameters, the benefits may not outweigh the added labor in SIT programmes for the management of mosquito vectors.